Validity and reliability of the wireless pressure sensor for aquatic activities and its ecological usefulness for swimming propulsion analysis - Coloretti, V.; Russo, G.; Fantozzi, S.; Cortesi, M. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
The thrust force (Ft) is only a fraction of the overall force exerted by the swimmer to move his body, and its enhancement is fundamental to improve velocity. Nevertheless, due to the complexity of the unsteady flow in swimming, how to measure the amount of this force is still under debate. Several approaches have been developed distinguished in indirect or direct methods. The latter methods extrapolate Ft directly, such as tethered-swimming or pressure sensors, while the former includes computational fluid dynamics, inverse dynamic estimation and Ft estimation from the swimmer`s active drag (Da)(Santos et al., 2021; Takagi et al., 2021). Because the direct assessment during free swimming remains difficult to quantify due to the swimmer`s progress, tethered swimming has become largely used to solve these issues. However, some differences were highlighted in fully-tethered swimming compared to freeswimming, such as the influence of the back acceleration during stroke pause (Takagi et al., 2021), or changes in swimming biomechanics (Samson et al., 2019). On the other hand, the challenge to assess Ft with less constraint and in natural swimming encouraged the group of Takagi and collaborators to propose an alternative technique based on the differential pressure of sensors placed on the palm and back of the swimmer`s hand (Takagi & Wilson, 1999). Subsequently, many devices based on the differential pressure approach are proposed in the literature (Koga et al., 2020; Tsunokawa et al., 2018), but the ecology of these devices remains questionable for the use of wires, taping, and gloves that impact the comfort and the sensibility of the swimmer. In recent years, advances in wireless technology can help the knowledge about swimming propulsion using an ecological approach and lower interferences with the swimming action (Fantozzi et al., 2022). Thus, this study aims to validate a wireless and wearable pressure sensor through i) a hydrostatic test to check the within-sensor, between-sensor, and day-by-day reliability of the device and the accuracy using the theoretical hydrostatic pressure (PRsT) as gold standard, ii) a hydrodynamic test to check the between-sensor reliability and the accuracy of the device using the theoretical hydrodynamic pressure (PRsT) as gold standard (PRdT). Furthermore iii), to check the ecological usefulness of these sensors for swimming propulsion, we conducted a comparison between the differential pressure force placed on the hands and the force exerted against a load cell during fully tethered swimming only-arms.